Ocio Night life promotion, gentrification and social distinction in downtown Sarajevo - Nofre i Mateo, Jordi; Martín i Díaz, Jordi (Anales de Geografía de la Universidad Complutense, 2009)
Night life promotion has become a widespread strategy in order to renew urban spaces in the downtowns of Western European cities. This strategy has recently been applied also to the downtown of Sarajevo. It has been turned into a consumption product and a symbol of social distinction for the new Muslim middle classes. This paper tries to show the relationship between clubbing and social exclusion in order to show how night life consumption is taking part of westernization of Sarajevo. This point of view stresses the consideration of night life consumption as one of the main mechanisms of self-identities’ constructions for these Sarajevo’s new muslim middle classes. This approach will allow think about to which extent the consequences of the Bosnia’s conflict have played a role in the process of gentrification in downtown Sarajevo.La vie nocturne est récemment devenue une des stratégies menées par les gouvernements locaux en Europe à renouveler ses espaces urbains, en particulier de ses centres urbains, comme Sarajevo. Cet article présente les résultats d’ordre qualitatif sur le terrain comment la consommation de la vie nocturne dans le centre historique de la capitale bosniaque contribue de manière significative à une occidentalisation espace avec la nouvelle classe moyenne urbaine ville musulmane. Une vision culturelle de ce processus permettra à un coup d’oeil sur les stratégies possibles gentrification urbaine et l’assainissement sociales liées à l’espace de plus en plus l’islamisation de la ville. Nous concluons l’article offre une chance d’envisager l’après-guerre de la fin des années 1990 comme un élément gentrificación la suite.
Keywords: Night life promotion; Clubbing; Muslim new middle classes; Gentrification; Sarajevo; Vie nocturne; “Clubbing”; De nouvelles classe moyenne musulmane; La gentrification